Pengembangan Buku Cerita Bergambar Berbasis Kearifan Lokal Untuk Meningkatkan Minat Baca Siswa Kelas VI Sekolah Dasar - Nurwahida, Nurwahida; Syatriana, Eny; Adam, Andi (Jurnal Ilmiah Global Education, 2025)
The objectives of this study are: (1) to develop a picture book based on local wisdom that is valid, practical, and attractive for students in the sixth grade of elementary school, and (2) to determine the effectiveness of the use of these products in increasing students ' reading interest. This type of research is Research and Development using ADDIE Development model (Analysis, Design, Development, Implementation,and Evaluation ). The subjects of the study consisted of 15 sixth grade students in one of the elementary schools in Pangkajene and Kepulauan Regency. The instruments used included expert validation sheets (material, media, language), practical response questionnaires by teachers and students, and reading interest questionnaires given before and after the intervention. Data were analyzed using descriptive statistical techniques and inferential statistics. The results showed that: (1) the picture story book products developed were declared “very Valid” by experts and “very practical” to be used by teachers and students in learning. (2) this product is proven to be effective in increasing students ' reading interest. This is evidenced by the increase in the average score of students ' reading interest from 47% (medium category) at the time of pre-test, to 81% (very high category) at the time of post-test. (3) the results of the paired t-test showed a statistically significant difference with the T-value: (9,18) > Ttable: (2,145), which confirmed that the increase in reading interest was an impact of the intervention given.